The Influence of Sandpaper Letters Media to Improve the Letter Recognition Skills of Children with Mild Mental Disability - Nurjanah, Tuti; Wida Rachmiati; Imas Masto’ah (COMPETITIVE: Journal of Education, 2025)
This research aims to find out whether there is a difference in the ability to recognize letters of mentally retarded students before and after using sandpaper letters media in class III SKh Negeri 01 Serang City. This research is non-parametric research with the type of research used in this research being pre-experiment using a one group pretest-posttest research design with a sample of five students. The data collection instrument is a test consisting of 10 questions that have been previously validated. The use of sandpaper letters as a medium to introduce letters to mentally retarded students resulted in an average of 81. Then analyzed using statistical testing using the Wilcoxon test, the asymp.sig (2-tailed) value was 0.043 and was smaller than the α value, namely 0.05. However, the difference between the asymp.sig (2-tailed) value and the α value is only 0.007, so the influence produced by sandpaper letters media is not large enough on the ability to recognize letters of children with mild mental retardation